2017
DOI: 10.2147/dnnd.s143989
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte membrane in the evaluation of neurodegenerative disorders

Abstract: Neurodegenerative diseases have many similar pathological conditions, and very few studies exist which detail their molecular features. Proteins like Na+/K+-ATPase (NKA), α-spectrin (SPTA) and drebrin have been reported to be involved in the integrity of neuronal cell membrane and their functions. Furthermore, recent studies have highlighted their implication in neurodegeneration. In the current study, we wanted to identify the role of NKA, SPTA and drebrin in the erythrocyte membranes obtained from the blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(23 reference statements)
1
6
0
Order By: Relevance
“…However, another study revealed lowered erythrocyte deformability with accompanied additional hemorheological abnormalities in patients suffering from Alzheimer’s disease when compared with control subjects [ 50 ]. In patients suffering from Parkinson’s disease, a significant reduction in the expression of Na,K-ATPase in erythrocytes was correlated with the significance of clinical features such as bradykinesia [ 51 ].…”
Section: Erythrocyte Nak-atpase and Deformability In Various Patho/physiological Situationsmentioning
confidence: 99%
“…However, another study revealed lowered erythrocyte deformability with accompanied additional hemorheological abnormalities in patients suffering from Alzheimer’s disease when compared with control subjects [ 50 ]. In patients suffering from Parkinson’s disease, a significant reduction in the expression of Na,K-ATPase in erythrocytes was correlated with the significance of clinical features such as bradykinesia [ 51 ].…”
Section: Erythrocyte Nak-atpase and Deformability In Various Patho/physiological Situationsmentioning
confidence: 99%
“…Furthermore, in this current study, I have provided compelling evidence that NKA activity is vital for normal brain development and loss of NKA activity is associated with cognitive impairment, neurological and developmental disorders [14,15,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86]. Indeed, loss of NKA activity represents an interconnected molecular function in neurodevelopmental and neuropsychiatric and neurodegenerative disorders including; Down syndrome, Alzheimer’s, Parkinson’s and Huntington’s disease, as well as epilepsy, autism, schizophrenia, mood and depressive disorders.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, a great body of evidence associates neurotoxicity with a reduction of NKA activity, suggesting that reduction in NKA activity may be a link between several common neurotoxic mechanisms [14,15,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79]. Loss of NKA is associated with autism [65,66,69]; Alzheimer’s disease [66,80,81]; Parkinson’s disease [82]; amyotrophic lateral sclerosis [70,82]; Down syndrome and Huntington’s disease [69]; depression and mood disorders [71,72,73,74]; bipolar disorder [14,75,76] and schizophrenia [15,77,79], as well as in animal models of depression [83,84]. Interestingly, NKA activity has been found to be significantly lower in subjects with phenylketonuria [85], a disease associated with intellectual disability, seizures, behavioural problems and mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…We proposed that this discrepancy might be caused by a difference in motor subtypes and severity of PD [32,33], as well as the small sample size of this study. Erythrocytes are emerging as a valid peripheral model for the study of aging-related pathologies [34,35]. Evidence indicates that erythrocytes lose all of their organelles when they mature, resulting in a lack of potential to replace proteins that have lost their functions and making them highly sensitive to any aberrations [36][37][38].…”
Section: Discussionmentioning
confidence: 99%